Sei sulla pagina 1di 71

Geometrical Interpretation of CMVT:

A geometrical interpretation may be given for the theorem as follows. Let a plane curve be represented Parametrically by the equations x=g(t) and y=f(t), where a<t<b. The slope of the curve for a given t is

y

0

t=c

t=a

t=b

x

(1)

(2)The constant

is the slope of the straight line joining the points on the curve corresponding to t=a and t=b, respectively. The theorem says that two slopes (1) and (2) are equal for at least one value of t between a and b.

Q1. in CMVT, if that c is independent of x.

, show

Solution. Since both f(x) and g(x) are continuous on [a, b] and f’(x) and g’(x) exist in (a, b) and g’(x)≠ 0 in (a, b), therefore we can apply CMVT. According to CMVT, we get

=>a+b = 2c =>c= (a+b)/2 Therefore c is independent of x.

Partial Differentiation:

Consider u= f(x,y). Here x and y are independent variables and u is dependent variable. In practical many situation arises where a variable depends on more than one independent variable.

The

differentiation

u

w.r.t.

x

treating

y

as

a

constant is called the partial derivative of u w.r.t. x

and denoted as

Analytically,

if exists.

Similarly,

if exists.

Homogenous Function:

Definition: A function f(x,y) is said to be homogenous of degree n if it can be express in the form or

For example, Let z = x 2 +xy+y 2 = x 2 (1 + y/x + y 2 /x 2 ) =x 2 .Ф(y/x) Or, z = y 2 (x 2 /y 2 + x/y + 1) = y 2 .Ф(x/y) In either cases z is homogenous of degree 2.

ForFor moremore thanthan 22 variables,variables, itit cancan bebe expressedexpressed as,as, f(x,y,z)= x n 1 (y/x, z/x)

Or

Or

y n 2 (x/y, z/y) z n . Ф 3 (x/z, y/z)

EULER’S THEOREM: If f(x,y) be homogenous function of x and y of degree n, then

Proof: Since f(x,y) is homogenous function of degree n.

Therefore,

Let f(x,y) =

= x n .Ф(t), where t = y/x.

So,

And

Definition:

Implicit Function:

An implicit

function x and y

is

an

equation of the form f(x,y)=0 which is not necessarily be solved for one of the variables in terms of others explicitly that is say x in terms of y. For example, X 3 +y 3 -3axy=0 is an implicit function of x and y.

In contract, when y is directly expressed in terms of x, say y=f(x), then y is called as explicit function.

Partial Differentiation of an implicit function:

Let f(x,y,z)=0 represents an equation of an implicit function of three variables x, y and z.

(a) Determination of

:

Assuming z=f(x,y) then differentiating partially f(x,y,z)=0 with respect to x and y respectively, we get.

Provided

and

(b) Determination of

:

Assuming

f(x,y,z)

x=f(y,z)

then

by

differentiating

z

partially

with

respect

to

and

y

respectively , we get .

Provided

and

(c) Determination of

:

Assuming y=f(x,z) then by differentiating partially f(x,y,z)=0 w.r.t. x and z respectively, we get.

Provided

and

Example 1. Find

Solution: Let, f(x, y,z)= Differentiating (1) partially w.r.t. x, we get

………………………(1)

Differentiating (1) partially w.r.t. z, we get

Differentiating (1) partially w.r.t. y, we get

Total Derivative:

y, which has

continuous partial derivatives w.r.t. x and y. Let be differentiable

function of t, then the composite function of t and

is differentiable function

Let u = f(x,y) be a function of two independent variables x and

Here ,

independent variables. In general form of this rule for functions of several independent variables like

is called total derivative of u. Equation (1) is called chain rule for two

can be written as,

Corollary 1. If u=f(x,y) is a function of two independent variables x and y, y is a function of x, y=g(x), then chain rule (1) can be written as follows,

Corollary 2. If u=f(x,y) is a function of two independent variables x and y, and if x=Ф 1 (t 1 , t 2 ), y=Ф 2 (t 1 , t 2 ) then the composite function u=f[Ф 1 (t 1 , t 2 ), Ф 2 (t 1 , t 2 )] is a function of t 1 and t 2.

If x, y and f are differentiable function, then we get,

Generalizing, chain rule (4) for

We get,

… … … … … … … … … … … …

as total derivative for

Example.1 Find

u= 3x+xy-y 2 where, x=cos3t, y=sin3t.

Solution: Here u= 3x+xy-y 2

Also, x= cos3t y= sin3t

= (3+y).(-3sin3t) + (x-2y).(3cos3t)

= (3+sin3t)(-3sin3t) + (cos3t-2sin3t)(3cos3t)

= -9sin3t-3sin 2 3t + 3cos 2 3t - 6sin3t.cos3t

= -9sin3t-3sin 2 3t+3(1-sin 2 3t) – 3(2sin3t.cos3t) = -9sin3t – 6sin 2 3t + 3 - 3sin6t

= -9sin3t + 3cos6t – 3sin6t.

Example 2. If z=f(x,y), prove that if x=e u +e -v , y=e -u - e v then

Solution: Here we can write the chain rule as

z

x

y

u
v
Fig.1.2

Now (1)-(2), we get,

Hence proved.

Laplace Operator or Laplacian:

The Laplace operator is a second order differential operator in the n-dimensional Euclidean space, defined as the divergence of the gradient .Thus if f is a twice-differentiable real-valued function, then the Laplacian of f is defined by

Equivalently, the Laplacian of f is the sum of all the unmixed second partial derivatives in the Cartesian coordinates x i

… … … … … (2)

Notes:

(1) Let x 1 , x 2 ,… … x n be a system of Cartesian coordinates on a n-dimensional Euclidean space, and let i 1 , i 2 ,… … i n be the corresponding basis of unit vectors. The divergence of a continuously differentiable vector field f = g 1 i 1 + g 2 i 2 + … …+ g n i n is defined to be the scalar-valued function:

(2) The gradient (or gradient vector field) of a scalar function is denoted where (the nabla symbol) denotes the vector differential operator, del. The notation grad(f) is also used for the gradient. The gradient of f is defined to be the vector field whose components are the partial derivatives of f. That is:

…. …. … … … (4)

Here the gradient is written as a row vector, but it is often taken to be a column vector.

(3)

symbol.

Vector

differential

operator

(4) Laplace operator or Laplacian symbol.

called

nabla

called tebla

Applications of Partial Differentiation:

1. Jacobians and their Applications.

2. Taylor’s Theorem for functions of two variables.

3. Error and Approximation.

4. Maxima and Minima.

6. Lagrange’s method of undetermined multipliers.

1. Jacobians and their Applications:

Defination1: (2-D case): If u = f(x, y) and v = g(x, y) be differentiable functions of two independent variables x and y, then the jaconian of u and v w.r.t.

x and y is denoted by as follows,

and is defined

Defination2:(3-D Case): If u = f(x, y, z), v = (x, y, z) and w = (x, y, z) be differentiable functions of three independent variables x, y and z, then the Jacobian of u, v, w w.r.t. x, y, z is denoted by and is defined as follows,

Thus in general (n-D Case) if u 1 = f 1 (x 1 , x 2 , … …, x n ) u 2 = f 2 (x 1 , x 2 , … …, x n ), … … … … … … … … … …, u n = f n (x 1 , x 2 , … …, x n ),

be

differentiable

functions

variables x 1 , x 2 , … …, x n then

of

n-independent

Example1: Find

when x = r.cosθ, y = r.sinθ.

Solution: Here x = r.cosθ and y = r.sinθ. Now we have,

= r.cos 2 θ+r.sin 2 θ =r(cos 2 θ+sin 2 θ) =r.

Example2: If x= r.sinθ.cosφ, y = r.sinθ.sinφ,

z = r.cosθ, find

.

Solution: Here given that, x= r.sinθ.cosφ, y = r.sinθ.sinφ, z = r.cosθ. Now we have,

= r 2 sinθ.

Properties of Jacobians:

1). If J is the Jacobian of u, v w.r.t. x, y and J’ is the Jacobian of x, y w.r.t. u, v, then JJ’ = 1 that is,

Proof: Let, u = f(x, y) and v = g(x, y) ………………

(1)

Solving (1) for x and y, we get x = φ(u, v) and y = ψ(u, v) ……………….(2) Differentiating (1) partially w.r.t. u and v gives,

Now,

Using (3) to (6), we get

Hence proved.

In general, the property can be written as

If u 1 = f 1 (x 1 , x 2 , … … x n ), u 2 = f 2 (x 1 , x 2 , … … x n ), … … …

… u

= f (x

n

x )

n

.

x

n

1 ,

2 ,

Note:

J’

is

known

as

inverse

Jacobian of J and vice versa.

transformation

2).

composite functions): If u, v are functions of r, s and r, s are functions of x, y then

Chain

rule

of

Jacobian

(Jacobians

of

Proof: Here, u and v are composite functions of x and y. Differentiating u and v partially w.r.t. x and y, we get

Similarly,

Now,

Hence proved.

using (1) to (4)

In general, the property can be written as

If u 1 , u 2 , … …, u n are functions of r 1 , r 2 , … …, r n are functions of x 1 , x 2 , … …, x n .

 3). If functions u, v, w of three independent functionally related or x, dependent iff variables y, z are

4). If the functions u 1 , u 2 , …, u n of the variables x 1 , x 2 , …, x n be defined by the relations u 1 = f 1 (x 1 ), u 2 = f 2 (x 1 ,x 2 ), u 3 = f 3 (x 1 , x 2 , x 3 ) and so on u n = f n (x 1 , x 2 , … …, x n ), then

Proof: Given, u 1 = f 1 (x 1 ).

u 2 = f 2 (x 1 ,x 2 ). and so on.

Now,

=

Example: If x = u(1-v), y = uv, evaluate

and

. Also verify jj’=1.

Solution: Here, x = u(1-v) and y = uv.

Now, x=u(1-v), y=uv solving them we get, u = x+y and v=y/(x+y)

Hence verified.

2. Taylor’s Theorem for functions of two variables.

Taylor’s series is useful to approximate a function in the neighborhood of a point. It is widely used in many disciplines like engineering, science, etc. to establish continuous models. It is also the mainstay of many numerical techniques. Statement: If f(x, y) and all its partial derivatives upto the n th order are finite and continuous for all points (x, y), where a ≤ x ≤ a+h, b ≤ y ≤ b+k, then

Alternate forms of Taylor’s series:

1.) In suffix notation, we get

2.) Putting x = a and y = b in (1), we have

3.) Putting a+h = x and b+k = y in (2), we get

Which expands f(x,y) in powers of (x-a) and (y-b) and is known as Taylor’s series or Taylor’s expansion or Taylor’s series expansion of f(x,y) about the point (a,b).

Example: Use Taylor’s series to expand sinx.cosy in powers of (x-π/3) and (y-π/4). Solution: Here, x-a = x - π/3. and y-b =y - π/4

=> a = π/3

=> b = π/4

Let, f(x, y) = sinx.cosy

=> f(π/3, π/4) = √3/2√2.

f x (x, y) = cosx.cosy => f x (π/3, π/4) = 1/2√2. f y (x, y) = -sinx.siny => f y (π/3, π/4) = -√3/2√2.

f xx (x, y) = -sinx.cosy => f xx (π/3, π/4) = -√3/2√2. f xy (x, y) = -cosx.siny => f xy (π/3, π/4) = - 1/2√2. f yy (x, y) = -sinx.cosy => f yy (π/3, π/4) = -√3/2√2. … … Now, the Taylor’s series in powers of (x - π/3) and (y - π/4) is given by

… … …

… … … … …

… … …

3.Errors and Approximations:

Let u be some physical quantity of interest depends on two measurable quantities x and y by the relation u = f(x, y). It is obvious that any change ∆x in x and ∆y in y will propagate the overall error ∆u in u and is given by ∆u = ∆f = f(x+∆x, y+∆y) – f(x,y). Now , expanding f(x+∆x, y+∆y) using Taylor’s series, we have

For

small

values

approximately

of

∆x

and

∆y,

we

have

This formula is useful for finding overall error in f(x,y) if the small errors in x and y occurs. It can easily be generalized for functions more than two variables approximately as

Where f is the function of x, y, z, t, …. … As we know that the error occurs in ∆x and ∆y may be positive or negative, therefore, the maximum error in f if given by

And in general,

If f is a function of x, y, z, t, … … …

Note:

(i)

df

in

(1)

and

(2)

above

known

as

approximate error in f while dx, dy, … … are known as actual (Absolute) errors in x, y, …., respectively.

(ii) dx/x, dy/y, … …, are known as relative errors (proportinal error) in x, y,…. …. ,respectively.

(iii) (dx/x).100 and (dy/y).100 are known as percentage errors in x and y respectively.

Example1:

differentials

approximate value of √8(65) 1/3.

Using

find

the

Solution: Let, f(x, y) = x 1/2 y 1/3. Choosing x = 9, y = 64 with decrease 1 in x and increase 1 in y. Now we have,

Here ∆x = -1 and ∆y = 1, putting these values we have,

Thus, change in x and y, decrease the value of the

function by

.

Therefore, Example2: The two resistors x and y are connected in parallel so that the total resistance R is given by xy/(x+y). If x and y are measured to be 200Ω and 300Ω respectively, with the increase of 1.5Ω in x and decrease of 4Ω in y, find the change in R. Solution: According to the given question, we get

x=200Ω

y=300Ω

Here,

Similarly,

Now ,

Here, x = 200Ω, y = 300Ω, ∆x = 1.5Ω, ∆y = -4Ω putting these values we get,

Therefore the decrease in R is 0.1Ω.

4.Maxima and minima of a function of

two variables:

Definition: Consider a function f(x, y) of two variables x and y and a point (a, b) and the neighborhood points (a+h, b+k). The value f(a, b) is said to be (i) maximum if f(a, b) > f(a+h, b+k) and (ii) minimum if f(a, b) < f(a+h, b+k).

which either a

maximum or a minimum is called an extremum

Extremum point: A point (a, b)

point.

Theorem1: The necessary conditions for f(a, b) to be an extremum value of “f” are that

f x (a, b) = 0 and f y (a, b) = 0

The point (a, b) is called a stationary point and the value f(a, b) is called the stationary value. Theorem2: The sufficient conditions for the

stationary value f(a, b) to be an extremum value as follows:

Let f xx (a, b) = A, f xy (a, b) = B, f yy (a, b) = C , then

1. If AC-B 2 > 0 and A (or C) < 0, then f(a, b) is a maximum value.

2. If AC-B 2 > 0 and A (or C) > 0, then f(a, b) is a minimum value.

3. If AC-B 2 < 0, then f(a, b) is neither a maximum nor a minimum value. But it a saddle point.

4. If AC-B2= 0 then no conclusion can be drown about maximum or minimum and further investigation is needed.

Note: Every extremum value is a stationary value but converse is not true.

Stationary point or Critical point: A point (a, b) is said to be stationary point of “f” if (i) at (a, b) both f x and f y are zero, or (ii) it is a boundary point of the domain. Working rules for finding extremum values of a function f(x, y):

.

1. Find

2. Find points (x, y) for which This gives the stationary points.

3. At each stationary point, evaluate values of

.

Saddle point or minimax point: In mathematics, a saddle point is a point in the domain of a function of two variables which is a stationary point but not a local extremum. At such a point, in general, the surface resembles a saddle that curves up in one direction, and curves down in a different direction (like a horse saddle or a mountain pass). In terms of contour lines, a saddle point can be recognized, in general, by a contour that appears to intersect itself. For example, two hills separated by a high pass will show up a saddle point, at the top of the pass, like a figure-eight contour line.

Example1: Examine the function f(x, y) = 2x 4 +y 2 -x 2 -2y for maxima and minima.

Solution: Here, f(x, y) = 2x 4 +y 2 -x 2 -2y. f x = 8x 3 -2x, and f y = 2y-2. For stationary points, we have f =0

x

,

f

y

= 0.

Therefore, 8x 3 -2x = 0 and 2y-2 = 0. Which implies points (0, 1), (1/2, 1), (-1/2, 1)

Now A = f xx = 24x 2 -2,

B = f xy = 0,

C = f yy = 2.

Case1: At the point (0, 1), AC-B 2 = (-2)(2)= -4<0.

Therefore (0. 1) is a saddle point.

Case2: At the point (1/2, 1), AC – B 2 = (4)(2)-0=8>0 and A=4>0. Therefore (1/2, 1) is a minimum point and the minimum value of the function is -9/8. Case3: At the point (-1/2, 1), AC-B 2 = (4)(2)-0= 8>0 and A=4>0. Therefore (-1/2, 1) is a minimum point and the minimum value of the function is -9/8.

6.Lagrange’s Method of Undetermined Multipliers:

This method is more useful for finding the stationary points of the function subject to the given constraint with the introduction of unknown constant(s) λ, known as Lagrange Multiplier. The main drawback of this method is that it gives no information regarding the nature of the stationary points. This fact is to be determined from the physical or geometrical consideration of the problem and which in some cases may be difficult to comprehend.

a function of three

independent variables x, y, z which are connected by the relation g(x, y, z) = 0. [ g(x, y, z)=0 is called constraint.].

Let, u=f(x, y,

z),

be

The Lagrange’s function is given by

F(x, y, z) = f(x, y, z)+λg(x, y, z)……………………(1)

Where λ is the arbitrary constant. Then dF = 0 implies that,

f x +λg x =0, f y +λg y =0, f z +λg z =0 ……………………(2)

This procedure is only for one constraint.

If there are 3 constraints, then the Lagrange’s function is given by, F(x, y, z) = f(x, y, z)+λ 1 g 1 (x, y, z)+λ 2 g 2 (x, y, z)+λ 3 g 3 (x, y, z) ……………………………………………… (3) Where, g 1 (x, y, z)=0, g 2 (x, y, z)=0,and g n (x, y, z) =0 are constraints. Then dF=0 implies that f x 1 g 1x 2 g 2x + λ 3 g 3x = 0 ……………………………… (4) f y 1 g 1y 2 g 2y + λ 3 g 3y = 0 ……………………………….(5) f z 1 g 1z 2 g 2z + λ 3 g 3z = 0 …………………………………(6) Then solve the equations (4), (5) and (6) to find out the values of λ 1, λ 2 and λ 3. Put the values of λ 1, λ 2 and λ 3 in the equations (4), (5) and (6) to get the values of x, y and z. Finally put the values of x, y and z in the given function.

Working rule for the Lagrange’s Method of undetermined multipliers:

Step1: Construct the Lagrange’s function[F(x, y, z)]. Step2: Find the differential of Lagrange’s function (dF). Step3: Consider, dF = 0 for stationary values. Here we will get equations (4), (5) and (6). Step4: Solve the equations (4), (5) and (6) to get the values of λ. Step5: Put the values of λ in equations (4), (5) and (6) to get the values of x, y and z.

put the values of x, y and z in the

Step6: Finally given function.

Example1: Find the minimum value of x 2 +y 2 +z 2 , given that ax+by+cz = p. Using Lagrange’s method.

Solution: Let u = x 2 +y 2 +z 2 and g(x,y,z) = ax+by+cz-p=0. ……………………… (i) The Lagrange’s function is given by F(x, y, z) = (x 2 +y 2 +z 2 )+λ(ax+by+cz-p) For stationary values, dF=0 gives, 2x+λa=0 ……………………………………………….(ii) 2y+λb=0 ………………………………………………(iii) 2z+λc=0 ……………………………………………….(iv)

Now , (ii).x+(iii).y+(iv).z implies that 2(x 2 +y 2 +z 2 )+λ(ax+by+cz)=0 => 2u+λp=0, using (i) =>λ=- 2u/p Putting this value in (ii), (iii) and (iv), we get x = au/p, y = bu/p, z = cu/p. Substituting these values of x, y, and z in the given function, we have u= u 2 (a 2 +b 2 +c 2 )/p 2 => u = p 2 /(a 2 +b 2 +c 2 ), neglecting the trivial case u = 0.

As we know that the perpendicular distance is

always
minimum.
Therefore,
the
length
of the
perpendicular
from
origin
o
on
ax+by+cz=p is given by
u (min) = p 2 /(a 2 +b 2 +c 2 ).
the plane
. Hence
O(0,0,0)
ax+by+cz=p
(x, y, z)

Example2: Find the maximum value of x 2 y 3 z 4 given that 2x+3y+4z=a. using Lagrange’s method.

Solution: The Lagrange’s function is given by F(x, y, z) = (x 2 y 3 z 4 )+λ(2x+3y+4z-a). For sationary values, dF = 0 gives 2xy z +2λ = 0. ……………………………………………

3x 2 y 2 z 4 +3λ = 0. …………………………………………….(ii) 4x 2 y 3 z 3 +4λ = 0. …………………………………………… (iii) Now (i).x+(ii).y+(iii).z, implies that

λ(2x+3y+4z) = -9x 2 y 3 z 4

3

4

(i)

λ

-9x 2 y 3 z 4

/a, using

=>

=

2x+3y+4z=a.

Substituting this value of λ in (i), (ii) and (iii), we get, x = y = z = a/9. Thus maximum value of x 2 y 3 z 4 is

.